A STUDY OF INVESTMENT BEHAVIOUR OF HOUSEHOLDS WITH REFERENCE TO NAGPUR CITY - Gupta, Shwetam; Jambhulkar, Shobha (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
The research will examine the various investment instruments preferred by households, the factors influencing investment decisions, and the level of financial literacy among households in Nagpur. Investment had its indirect repercussions. The study focuses on the various sources and the extent of income of the different groups of the households and on the attitude of the households on the various investments they have at their disposal. The Chi-square test and analysis are used to evaluate the objectives of the study. The researchers have found out how for the association between the various factors like age, gender, educational qualification, marital status, type of family, size of the family, nature of employment, years of service and the like and the investment pattern is significant. Based on the various findings of the study the researchers have given useful and constructive suggestions. The findings of this research will provide valuable insights into the investment behavior of households in Nagpur and can be used by financial institutions and policy makers to design appropriate investment products and financial literacy programs. The results of this study will also contribute to the larger body of literature on household investment patterns and financial behavior.